Why English teaching truth on digital trends as an effort for effective learning and evaluation: opportunities and challenges: analysis of teaching English - Susanty, Lela; Hartati, Zainap; Sholihin, Rahmat; Syahid, Abdul; Liriwati, Fahrina Yustiasari (Linguistics and Culture Review, 2021)
This study aims to gain a comprehensive understanding of why foreign language teaching, especially English, believes in using digital trend applications to improve learning effectiveness and evaluation validity in the perspective of current opportunities and challenges. So, for this purpose, the step we take is to examine hundreds of scientific reports on teaching English in many international contexts to answer the questions above with valid and reliable principles. Because Indonesia is currently in the process of implementing restrictions on public movements to respond to Covid-19, we have decided that this study will depend on secondary data through a Google search engine on scientific journals such as Willey, Taylor & France, Google Book, ERIC, Sagepub, and other international journals. Our data is analyzed with an unusual approach: coding, evaluation, interpretation, and drawing of results that answer the problem of the study. Discussing the results, we found that teaching English believes in digital applications to improve teaching and evaluation effectiveness because these applications have proven to be very innovative and effective in increasing the world's productivity globally. Hopefully, this finding helps develop future teaching studies.